Research achievements in pearl millet (Pennisetum glaucum) - BHATNAGAR, S K; YADAV, O P; GAUTAM, R C (The Indian Journal of Agricultural Sciences, 2013)
Pearl millet [Pennisetum glaucum (L.) R. Br. emend. Stuntz] is an important crop of dryland agriculture in India butit also responds well to irrigation and improved management conditions. Hybrids in pearl millet were released in Indiain the sixties. They were widely adopted and mainly instrumental in increasing the productivity. However, hybrids had recurring problems of downy mildew (Sclerospora graminicola) primarily because of their narrow genetic base and utilization of limited number of parental lines. during seventies in hybrid breeding. However, presently highly diverse male-sterile lines and pollinators are being developed and utilized. Population-improvement programmes werestrengthened to provide backup to hybrid breeding. Germplasm accessions with stable resistance to various diseases were identified and utilized in breeding disease-resistant cultivars. Great headway was made in understanding the biology and epidemiology of important diseases which helped in developing suitable control measures. Agronomicresearch led to the establishment of various agro-techniques for different pearl millet-growing areas. Proper'agronomicrecommendation made it possible to harness the potential yield of high-yielding cultivars including hybrids andcomposites. The article highlights the progress made in increasing the production and productivity of this crop during the last 50 years.